Antimicrobial resistance: strategies for effective messaging - Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association (MIMPA), 2024)
Antibiotic resistance threatens to render our most potent medical treatments ineffective, jeopardising not only individual health but also public health on a global scale. Yet, despite its severity, antibiotic resistance is often misunderstood or overlooked by the public. This e-book aims to bridge that gap by providing clear, concise, and persuasive messaging strategies to engage diverse audiences. Whether you are a healthcare professional, educator, policymaker, or simply someone passionate about raising awareness, the insights and techniques outlined in this ebook will empower you to convey the urgency of antibiotic resistance in a compelling and impactful manner. Together, we can inspire action, promote responsible antibiotic use, and safeguard the effectiveness of these life-saving medications for generations to come.